2021
DOI: 10.1158/0008-5472.can-20-3454
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Identification of Elevated Circulating CDCP1 in Patients Years before Onset of Lung Cancer

Abstract: Increasing evidence points to a role for inflammation in lung carcinogenesis. A small number of circulating inflammatory proteins have been identified as showing elevated levels prior to lung cancer diagnosis, indicating the potential for prospective circulating protein concentration as a marker of early carcinogenesis. To identify novel markers of lung cancer risk, we measured a panel of 92 circulating inflammatory proteins in 648 prediagnostic blood samples from two prospective cohorts in Italy and Norway (w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
1
23
1
Order By: Relevance
“…This is the first study to reveal the association of CDCP1 with acquired resistance to osimertinib in cancer cells. Recent prospective proteomics analysis by Dagnino et al has demonstrated that higher blood levels of CDCP1 protein are clearly associated with the risk of lung cancer 44 , suggesting the potential role of CDCP1 in onset of lung cancer. On the other hand, CDCP1 has been reported to enhance WNT/β-catenin signaling pathway through increased nuclear localization of β-catenin 45 .…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to reveal the association of CDCP1 with acquired resistance to osimertinib in cancer cells. Recent prospective proteomics analysis by Dagnino et al has demonstrated that higher blood levels of CDCP1 protein are clearly associated with the risk of lung cancer 44 , suggesting the potential role of CDCP1 in onset of lung cancer. On the other hand, CDCP1 has been reported to enhance WNT/β-catenin signaling pathway through increased nuclear localization of β-catenin 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Ikeda et al [28] conducted a multivariate Cox regression analysis of 200 lung adenocarcinoma patients and reported that high CDCP1 expression acts as an independent prognostic factor for OS and DFS. Dagnino et al [29] suggest that circulating serum levels of CDCP1 provide additional information on future lung cancer risk, especially in patients who had tobacco exposure. Although this study was different from our study in which they measured plasma CDCP1 levels, our results were similar in terms of the possibility of CDCP1 being an early diagnostic marker considering the high percentage of smoking patients in the CDCP1-positive group.…”
Section: Discussionmentioning
confidence: 99%
“…At least eight of the 36 markers have been previously reported to be associated with lung cancer in pre-diagnostic samples, including several well-known tumor markers such as CEACAM5/CEA and CA-125/MUC-16, 34 as well as IL6, CDCP1, CXCL9 and CXCL13. [36][37][38] However, most of the 36 proteins are newly identified pre-diagnostic markers of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest a role for these markers in tumor progression or an immune or inflammation response in lung tissue. Notably, CDCP1 was previously associated with an increased risk of lung cancer in pre-diagnostic blood, 38 is overexpressed in lung cancer tissue, 51 and is associated with metastases and poor prognosis. [51][52][53][54]…”
Section: Epidemiological Properties Of Identified Proteinsmentioning
confidence: 99%